Penerapan Prinsip Good governance dalam Sistem Pelayanan Publik Berbasis E-government di Rumah Sakit Haji Kota Medan - Zsazsa, Cut Sah Kha Mei; Dewi, Ratna Sari (Mahesa Research Center, 2025)
This article aims to analyze the application of Good governance principles in the E-government-based public service system at the Medan City Hajj Hospital. This study uses a qualitative descriptive approach, with data collection techniques through literature studies, direct observation, and in-depth interviews. Informants were selected purposively, consisting of the head of the server installation, computer operators, medical personnel, and health workers. The results of the study indicate that the application of Good governance principles in the E-government-based public service system at the Medan City Hajj Hospital has been running optimally, indicated by the fulfillment of three main indicators of Good governance principles: transparency, accountability, value for money, which have been reflected in the practice of accountable and efficient public services. In the aspect of public services, indicators such as public service, namely friendliness of officers, timeliness of completion, service costs, comfort, speed of service, fairness in service, clarity of officers, and service schedules have also been applied consistently and effectively. Meanwhile, the application of E-government shows a significant role in strengthening the governance system, especially in improving the quality of services, creating a competitive work environment, appreciating innovation, and achieving operational efficiency. This shows a strong integration between E-government and the principles of Good governance in supporting public services in the health sector.